The entrepreneur - Ajagu, Ausbeth (Lagos : Betcy Media, 2005)
This book is a response to the many unanswered questions besetting the prospects of the small, medium, and large-scale industries, which are leading players in entrepreneurship in Nigeria, the various efforts of the successive governments especially the Obasanjo Administration, and proffers lasting solutions from an informed private sector perspective.
"Secrets of getting to the top and staying there happily too; plus authentic profiles of select entrepreneurs and captains of industry in Nigeria"--Cover.
Includes bibliographical references and indexes.
gau 26/05/14
Loans
Keywords: Entrepreneurship; New business enterprises; Nigeria